Food of the yellowtail amberjack Seriola lalandi from the south-west Atlantic - Vergani, M. (2008)
Food of Seriola lalandi was mainly composed of juveniles of horse mackerel (Trachurus lathami) (%IRI=99.66) showing the species as carnivorous feeders predating on small pelagic organisms. ©2008 Marine Biological Association of the United Kingdom.